2021
DOI: 10.3126/jnarc.v7i1.36934
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Mitigates the Effects of Climate Change

Abstract: Intensive tillage based conventional agriculture have high global warming potential. Alternative to this, conservation agriculture (CA) systems utilize soils for the production of crops by reducing excessive tillage, maintaining crop residue on the soil surface, and adoption of crop rotations. The paper attempts to review the findings of CA based experiments under different cropping systems within and outside of the country. It has been found that CA increases and sustains the crop productivities, mitigates gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…More than 97% of the world's food supply is produced on land that emits GHGs when intensively tilled, fertilized, and/or grazed by animals [67]. Conversion of 76% of the croplands in the USA, for example, to conservation tillage could sequester as much as 286-468 million metric tonnes (MMTs) CO 2 e over 30 years showing that conservation agriculture could become a net sink for carbon [68] and play an important mitigation and adaptation role in climate change effects [69,70].…”
Section: Conservation Agriculturementioning
confidence: 99%
“…More than 97% of the world's food supply is produced on land that emits GHGs when intensively tilled, fertilized, and/or grazed by animals [67]. Conversion of 76% of the croplands in the USA, for example, to conservation tillage could sequester as much as 286-468 million metric tonnes (MMTs) CO 2 e over 30 years showing that conservation agriculture could become a net sink for carbon [68] and play an important mitigation and adaptation role in climate change effects [69,70].…”
Section: Conservation Agriculturementioning
confidence: 99%
“…Crop rotation function as biological drives also required for deepest layer of soil nutrients that helps to cultivate commercial crop. Crop rotation helps to uptake plant nutrients through diverse soil flora and fauna (Karki and Gyawaly 2021). Mixed cropping of legumes and maize do not help to conserve soil and nutrient loss in hills of central Nepal.…”
Section: Crop Diversity and Rotationmentioning
confidence: 99%
“…In hilly area, there are very limited source like crop residue used for livestock feed, lack of means of transportation that causes problem for loading and unloading the heavy agriculture machines and equipment, poor affordability of the farmers for machines and rain-fed agriculture that is very difficult to adopt the conservation agriculture based technologies by farmers (Karki and Shrestha 2014). The main factors for conservation agriculture adoption by farmers are lack of knowledge about conservation agriculture, insufficient farm machineries and tools, small land holdings, poor infrastructures, and lack of policy regarding conservation agriculture (Karki and Gyawaly 2021).…”
Section: Soil Cover and Water Retention (Mulch And Crop Residue)mentioning
confidence: 99%
“…Evidence shows that crops like wheat, maize, pulses, oilseeds, jute, and rice can be established and grown successfully through CA technology (Bell et al, 2018; Alamgir et al, 2015). However, previous studies revealed knowledge gaps, fragmented holdings, inadequate farm machinery, subsidy/project dependence, poor infrastructure, and lack of CA-friendly policy support (Chaudhary et al, 2022; Karki and Gyawaly, 2021) that are limiting the translation of the benefits of CA demonstrated in research to farms of the EGP.…”
Section: Introductionmentioning
confidence: 99%